ST13 polymorphisms and their effect on exacerbations in steroid‐treated asthmatic children and young adults. Issue 6 (June 2015) - Vijverberg, S. J. H.; Koster, E. S.; Tavendale, R.; Leusink, M.; Koenderman, L.; Raaijmakers, J. A. M.; Postma, D. S.; Koppelman, G. H.; Turner, S. W.; Mukhopadhyay, S.; Tse, S. M.; Tantisira, K. G.; et al.
Summary Background The clinical response to inhaled corticosteroids (ICS) is associated with single nucleotide polymorphisms (SNPs) in various genes. This study aimed to relate variations in genes in the steroid pathway and asthma susceptibility genes to exacerbations in children and young adults treated with ICS. Methods We performed a meta‐analysis of three cohort studies: Pharmacogenetics of Asthma Medication in Children: Medication with Anti‐Inflammatory effects (n = 357, age: 4–12 years, the Netherlands), BREATHE (n = 820, age: 3–22 years, UK) and Paediatric Asthma Gene Environment Study (n = 391, age: 2–16 years, UK). Seventeen genes were selected based on a role in the glucocorticoid signalling pathway or a reported association with asthma. Two outcome parameters were used to reflect exacerbations: hospital visits and oral corticosteroid (OCS) use in the previous year. The most significant associations were tested in three independent validation cohorts; the Childhood Asthma Management Programme (clinical trial, n = 172, age: 5–12 years, USA), the Genes‐ environment and Mixture in Latino Americans II‐ study (n = 745, age: 8–21, USA) and the Pharmacogenetics of adrenal suppression cohort (n = 391, age: 5–18, UK) to test the robustness of the findings. Finally, all results were meta‐analysed. Results Two SNPs in ST13 (rs138335 and rs138337), but not in the other genes, were associated at a nominal level with an increased risk of exacerbations in asthmatics using ICS in the three cohorts studied. In a meta‐analysis of all six studies, ST13 rs138335 remained associated with an increased risk of asthma‐related hospital visits and OCS use in the previous year; OR = 1.22 (P = 0.013) and OR = 1.22 (P = 0.0017), respectively. Conclusion and clinical relevance A novel susceptibility gene, ST13, coding for a cochaperone of the glucocorticoid receptor, is associated with exacerbations in asthmatic children and young adults despite their ICS use. Genetic variation in the glucocorticoid signalling pathway may contribute to the interindividual variability in clinical response to ICS treatment in children and young adults.